The everything guide to micro weddings : the ultimate source for planning a small and meaningful wedding - Martin, Katie, 1972- (Everything series, 2021)
"As more couples find that smaller weddings are more affordable, intimate, and meaningful, they're ditching the huge blowout receptions and opting for nontraditional nuptials with fewer than fifty guests. Whether it be the budget, the stress, or something else altogether, more and more couples are turning to micro weddings to tie the knot. With a smaller crowd, the focus shifts from "Is everyone having a good time?" to "This is the best day of my life!" Whether you want people to attend in person or will live stream the event, The Everything Guide to Micro Weddings covers everything from décor hacks, venue hunting, and tips from how to cut costs to how to gracefully tell the second cousin they're not invited. So skip the large affair and say 'I do' to The Everything Guide to Micro Weddings-a perfect match for those looking to make their big day, well, small"--